2020
DOI: 10.2478/acph-2020-0019
|View full text |Cite
|
Sign up to set email alerts
|

Potential antidiabetic and antioxidant activities of a heliangolide sesquiterpene lactone isolated from Helianthus annuus L. leaves

Abstract: AbstractHeliangolide is a naturally occurring sesquiterpene lactone and its derivatives are biologically active compounds present in most medicinal plants. This study evaluated the antioxidant and antidiabetic properties of a heliangolide sesquiterpene lactone isolated from Helianthus annuus L. leaves. The heliangolide sesquiterpene lactone was isolated through a combination of solvent-solvent partitioning, column chromatography, thin layer chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
(28 reference statements)
0
15
0
1
Order By: Relevance
“…The abovementioned correlations indicate the main role of phenolic compounds in the antioxidant activity of the extracts of the aerial parts of sunflowers at all growth stages. In the sunflower seeds and leaves, non-phenolic antioxidants have also been determined, including tocopherols and volatile compounds [27,45]. However, their presence in the extracts, in our study, was limited by the extraction conditions: the polar solvent and high temperature of the process.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The abovementioned correlations indicate the main role of phenolic compounds in the antioxidant activity of the extracts of the aerial parts of sunflowers at all growth stages. In the sunflower seeds and leaves, non-phenolic antioxidants have also been determined, including tocopherols and volatile compounds [27,45]. However, their presence in the extracts, in our study, was limited by the extraction conditions: the polar solvent and high temperature of the process.…”
Section: Resultsmentioning
confidence: 77%
“…Recent information about the secondary metabolites of sunflower leaves has been provided as a result of metabolomic studies, in which compounds from three chemical groups, including hydroxycinnamoylquinates, methyl-flavonoids and sesquiterpenoids, were detected [25,26]. Onoja et al [27] found that a sesquiterpene lactone, isolated from H. annuus leaves, had antidiabetic and antioxidant properties, but, to the best of our knowledge, the total antioxidant potential of sunflower leaves has not yet been estimated.…”
Section: Introductionmentioning
confidence: 99%
“… Compound Class Plant source Biological effects Mechanisms implicated Refs. 1 Enhydrin Melampolide Smallanthus sonchifolius Hypoglycemic ( in vivo ) Post-prandial glucose levels (↓) Inhibition of α-glucosidase Genta et al., 2010 ; Serra-Barcellona et al., 2017 2 Polymatin A Melampolide Smallanthus macroscyphus Hypoglycemic ( in vivo ) Post-prandial glucose levels (↓) Serra-Barcellona et al., 2014 3 20-dehydroeucannabinolide Heliangolide Helianthus annuus Antidiabetic ( in vivo ) Antioxidant ( in vitro ) Fasting blood glucose level (↓) DPPH radical and NO scavenging activities Onoja et al., 2020 4 Eremanthin Guaianolide Costus speciosus Hypoglycemic, and hypolipidemic ( in vivo ) Antioxidant ( in vivo ) Blood glucose levels (↓), HbA1c (↓), plasma insulin (↑), tissue glycogen (↑) TC, TG and LDL-C (↓); HDL-C (↑) TBARS levels (↓), GSH (↑), SOD, CAT and GPx (↑) in brain, liver, heart, kidney, and pancreas Eliza et al., 2009a , 2009b , 2010 5 Costunolide Germacrolide Costus speciosus 6 Alantolactone Eudesmanolide Inula helenium Antiinflammatory-associated to glucose intolerance and IR ( in vitro ) Antiinflamatory- obesity-induced IR ( in vitro ) Attenuates lipid accumulation ( in vitro ) Antiinflamatory- associated to diabetic nephropathy ( in vivo ) STAT3 inhibitor. Inhibition of the TLR4 gene expression.…”
Section: Search Strategymentioning
confidence: 99%
“…1 ). ( Onoja et al., 2020 ). Heliangolide SLns represent an isomeric form of germacranolides with a cyclodecadiene skeleton and double bonds at C1=C10 and C4=C5, which stereochemical configurations are trans, cis respectively ( Sülsen and Martino, 2018 ).…”
Section: Slns Isolated From Medicinal Plants and Their Potential Rolementioning
confidence: 99%
See 1 more Smart Citation